Image In The Artistic Expression Of The Spirit Of Children - Nabiyeva Zarina Nabiyevna (International Journal on Orange Technologies, 2021)
The article deals with the expression of the image of children in fiction and its figurative interpretations, including Antoine de Saint-Exupery the story of the "Little Prince" was considered. Special attention was paid to the study of interpretations of the relationship between children and adults